👤
a fost răspuns

[tex]Fie~a,b \in Q ~si~a,b \geq 0.Sa~se~demonstreze~ca: \\ a)daca~ \sqrt{a} + \sqrt{b} \in Q ,atunci~ \sqrt{a} ~si~ \sqrt{b} ~apartin~lui~Q. \\ b)daca~ \sqrt[3]{a} + \sqrt[3]{b} \in Q,atunci~ \sqrt[3]{a} ~si~ \sqrt[3]{b} ~apartin~lui~Q. \\ \\ Astept~o~verificare~la~raspunsul~urmator+rezolvare(daca~treb.): \\ a) \sqrt{a} + \sqrt{b} =x ,x\in Q |^2 \\ a+b+2 \sqrt{ab} =c^2 \\ \sqrt{ab} = \frac{c^2 -(a+b)}{2} \in Q \\ Deducem~ca~ \sqrt{a} ~si~ \sqrt{b} \in Q. \\ b)Am ~facut~exact~la~fel~doar~ca~ridic~la~cub. [/tex]

Răspuns :

[tex]\displaystyle Cazul~a=b~este~trivial,~atat~la~a),~cat~si~la~b). \\ \\ Tratam~cazul~a \neq b. \\ \\ a)~(\sqrt{a}+ \sqrt{b})( \sqrt{a}- \sqrt{b})=a-b \Rightarrow \sqrt{a}- \sqrt{b}= \frac{a-b}{\sqrt{a}+\sqrt{b}} \in \mathbb{Q}. \\ \\ Deci~(\sqrt{a}+ \sqrt{b})+(\sqrt{a}-\sqrt{b}) \in \mathbb{Q} \Leftrightarrow 2 \sqrt{a} \in \mathbb{Q} \Rightarrow \sqrt{a} \in \mathbb{Q}. \\ \\ Din~ \sqrt{a}+ \sqrt{b} \in \mathbb{Q}~si~\sqrt{a} \in \mathbb{Q}~rezulta~\sqrt{b} \in \mathbb{Q}.[/tex]

[tex]\displaystyle b) ~Notez~c= \sqrt[3]{a}+ \sqrt[3]{b} \in \mathbb{Q}. \\ \\ Atunci~c^3 \in \mathbb{Q} \Leftrightarrow a+b+3 \sqrt[3]{ab}(\sqrt[3]{a}+ \sqrt[3]{b}) \in \mathbb{Q}. \\ \\ Adica~a+b+3c \sqrt[3]{ab} \in \mathbb{Q}.~Dar~a,b,c \in \mathbb{Q} \Rightarrow \sqrt[3]{ab} \in \mathbb{Q}. \\ \\ c^2 \in \mathbb{Q} \Leftrightarrow \sqrt[3]{a^2}+2 \sqrt[3]{ab}+\sqrt[3]{b^2} \in \mathbb{Q} \Rightarrow \sqrt[3]{a^2}+\sqrt[3]{b^2}\in \mathbb{Q}.[/tex]

[tex]\displaystyle ( \sqrt[3]{a^2}+ \sqrt[3]{b^2} )^2 \in \mathbb{Q}.~Deci~a\sqrt[3]{a}+b\sqrt[3]{b} + 2 \sqrt[3]{a^2b^2} \in \mathbb{Q}. \\ \\ Rezulta~d=a \sqrt[3]{a}+b \sqrt[3]{b} \in \mathbb{Q}. \\ \\ ac \in \mathbb{Q} \Rightarrow d-ac \in \mathbb{Q} \Leftrightarrow (b-a) \sqrt[3]{b} \in \mathbb{Q}.~Dar~b-a \in \mathbb{Q^*},~si~deci \\ \\ \sqrt[3]{b} \in \mathbb{Q}. \\ \\ Apoi,~din~asta~si~din~\sqrt[3]{a}+ \sqrt[3]{b} \in \mathbb{Q}~rezulta~\sqrt[3]{a} \in \mathbb{Q}.[/tex]